SOYA BEANS PRODUCTION AND RURAL LIVELIHOODS: A CASE STUDY OF NTATUMBILA VILLAGE OF NAKONDE DISTRICT, ZAMBIA - Jackson Nyirenda; Brivery Siamabele; Valentine Kalonje; Themba Mapulanga; Rudo Phiri Mumba (International Journal of Educational Excellence and Innovation, 2025)
Rural societies have remained underdeveloped and impoverished due to challenges in generating the income necessary to improve their well-being. Traditionally, these communities consist of small holder farmers who primarily grow crops that only meet their subsistence needs. However, the cultivation of soya beans in rural areas has been argued to significantly enhance livelihoods. Soya bean farming has enabled small-scale farmers to diversify into growing additional crops, which have generated extra income for improved infrastructure, access to quality healthcare, and enhanced food security in rural communities. This study found that soya bean cultivation has the potential to uplift the rural livelihoods of small-scale farmers, largely due to its high market value. This market advantage has allowed farmers to diversify their agricultural activities, leading to broader improvements in community well-being. In Ntatumbila village, increased soya bean cultivation among small-scale farmers has resulted in higher income, better nutrition, affordable livestock feed, and improved housing infrastructure. The study concluded that soya bean cultivation holds significant potential to enhance rural livelihoods and food security. It called for coordinated efforts by the Ministry of Agriculture, civil society organizations focused on climate change, agro-financial institutions, and agro-dealers to develop strategies that support small-scale farmers in expanding soybean production to improve rural livelihoods and food security.